Current Genetics in Dermatology - Oiso, Naoki (IntechOpen, 2013)
This book presents current topics in genetics in the dermatologic field. Various skin disorders are inherited as mendelian inheritance. Genetic skin disorders are caused by mutations in the genes encoding proteins expressing in skin, skin appendages, melanocytes and immune-associated cells. Identification of genes and elucidation of function of the encoded proteins may provide novel strategies to overcome the disorders. We hope that this book offers sufficient current information in each disorder to scientists, physicians and dermatologists, and that novel therapies will be provided to affected individuals via these chapters.